Konsep Adab Menuntut Ilmu Perspektif Syaikh Muhammad Syakir Al Iskandari Dalam Kitab Washoya - Fathurahman Suryadi; Muhammad Habib Pasaribu; Aqbil Daffa Siahaan; Ahmad Sabri; Rully Hidayatullah (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to find out how the adab of students in studying according to the views of Sheikh Muhammad Syakir in the Washoya Al-Abaa' lil Abna. The type of research conducted is library research. The data collection technique is through documents related to the adab of studying according to the thoughts of Sheikh Muhammad Syakir. While the data examination technique uses the content analysis method. The results of this study explain that: 1) Sheikh Muhammad Syakir is an extraordinary scholar, one of whose works is the book Washoya Al-Abaa' lil Abnaa. 2) The adab of seeking knowledge in the book Washoya Al-Aba' Lil Abna by Sheikh Muhammad Syakir is a very good ethic that must be driven by students in seeking knowledge. Between the adab of seeking knowledge and the ethics of Islamic education, it has an important meaning that every level of education is expected to emphasize on good morals and manners. One of the principles applied to learn ethics is to provide appropriate learning and exemplify its application in life, so that in the development of fast-paced technology does not affect the ethics and attitudes of a person in an era that is running according to Islamic values.